AB1188 Patient Reported "Negative" Life Events That Cause Stress Can Impact Patient Reported Outcomes in Early Rheumatoid Arthritis; An Analysis of the Catch Study. (9th June 2015) - Bykerk, V.P.; Kim, Y.A.; Lin, D.; Bartlett, S.J.; Boire, G.; Hitchon, C.A.; Haraoui, B.; Keystone, E.; Tin, D.; Thorne, J.C.; Pope, J.; Salmon, J.
Abstract : Background: Stress plays a role in disease onset, activity, and exacerbation of inflammatory autoimmune diseases including rheumatoid arthritis (RA). The effect of stress on patient reported outcomes (PROs) has not been studied in early RA. Objectives: To evaluate the effect of stressful physical and psychological major life events on patient reported outcomes (PROs) at disease presentation and over one year in patients with ERA. Methods: Patients participating in CATCH (Canadian Early Arthritis Cohort), a prospective multicenter study, were queried about major life events that occurred in the year prior to study entry. Changes in PROs and in the RAPID 3 score over time were evaluated using generalized estimating equations for those exposed to psychological or physical stress. Survival curves of time to RAPID3 remission in stress/no-stress patients was compared using Log Rank Tests. Results: Of 1596 patients, 51% reported stress. Patients reporting prior stress were (mean, 95%CI) younger [53 (52, 54) vs. 55 (54, 56); p=0.001], more often female (77% vs. 69%; p<0.001), living alone (17% vs. 12%; p=0.005); fewer completed high school (41% vs. 48%, p=0.01). They reported higher levels of pain [5.8 (5.6-6.0) vs. 5.3 (5.1, 5.5); p<0.001], fatigue [5.7 (5.5, 5.9) vs. 4.8 (4.6, 5.0); p<0.001], worse function [HAQ-DI [1.1 (1.1, 1.2) vs. 1.0 (0.9, 1.0); p<0.001], and global disease assessment [60.2 (58.2, 62.2) vs. 55.7 (53.6, 57.8); p=0.002]. A significant, independent negative effect of psychological but not physical stress was associated with RAPID3 scores at BL, 6 and 12 months (p≤0.0008) (Table ). Fewer patients reporting prior psychological stress achieved a RAPID 3 remission (p<0.0017). Conclusions: Exposure to major stressful life events has significantly negative effects on PROs including pain, fatigue and function over time, and is associated with lower RAPID3 defined remission at 1 year. Sources of stress such as these should be elicited in the patient history and considered when interpreting response to therapy as assessed using PRO derived composite disease activity measures such as the RAPID3. Disclosure of Interest: V. Bykerk Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since the inception of CATCH. As of 2011, further support was provided by Hoffmann-LaRoche Ltd., UCB Canada Inc., Bristol-Myers Squibb Canada Co., AbbVie Corporation (formerly Abbott Laboratories Ltd.), and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.), Y. Kim: None declared, D. Lin: None declared, S. Bartlett: None declared, G. Boire: None declared, C. Hitchon: None declared, B. Haraoui: None declared, E. Keystone: None declared, D. Tin: None declared, J. C. Thorne: None declared, J. Pope: None declared, J. Salmon: None declared